PENGARUH STRATEGI BISNIS, UKURAN PERUSAHAAN, DAN MANAJEMEN LABA TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI INDONESIA - Raudatul Jannah; Wia Rizqi Amalia; Novika Rosari; Nor Hikmah; Dahliana Iskandar (KINDAI, 2026)
This study examines the effects of business strategy, company growth, and earnings management on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employed a quantitative approach using multiple linear regression analysis with IBM SPSS Statistics version 23. The population consisted of all manufacturing companies listed on the IDX, while the sample comprised 32 companies selected using purposive sampling. Business strategy was classified into two categories, namely prospector and defender. Company performance was measured using Return on Assets (ROA), whereas earnings management was measured using the Modified Jones Model. The results indicate that business strategy has a significant effect on company performance, while company growth and earnings management do not have a significant effect on company performance. The novelty of this study lies in the research period and the research object, which extend previous studies by providing evidence from Indonesian manufacturing companies during the 2021–2023 period. Keywords: business strategy; company growth; company performance; earnings management